2008
DOI: 10.1097/gco.0b013e328302143c
|View full text |Cite
|
Sign up to set email alerts
|

Thin endometrium in assisted reproductive technology

Abstract: Various recent modalities proposed for the treatment of thin endometrium seem to be useless and inefficient from an evidence-based medicine point of view. At the moment, evaluation of endometrium using different ultrasonographic markers seems to be superior to all those therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
3
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 72 publications
1
82
3
3
Order By: Relevance
“…The endometrium is essential for implantation and as such the thickness of the endometrium has been always considered as an index of quality [17]), especially in assisted reproduction where the selected embryos should be transferred ideally in a receptive environment. A thin endometrium it has been reported in 5 % of women <40 years of age and in 25 % of 41-45 years old women [18] and it has also been related to poor pregnancy outcome [20].…”
Section: Introductionmentioning
confidence: 99%
“…The endometrium is essential for implantation and as such the thickness of the endometrium has been always considered as an index of quality [17]), especially in assisted reproduction where the selected embryos should be transferred ideally in a receptive environment. A thin endometrium it has been reported in 5 % of women <40 years of age and in 25 % of 41-45 years old women [18] and it has also been related to poor pregnancy outcome [20].…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of these 11 pregnancies (eight miscarriages, two late terminations due to malformations and one live birth) demonstrated that these patients had a poor reproductive prognosis even if some endometrial thickening or implantation did occur. The failure of the different treatment modalities to improve the poor reproductive outcome in these patients is unfortunately in accordance to published data [20]. The high pregnancy loss rate might be the consequence of an endometrial cellular or molecular defect which is presently beyond our recognition.…”
Section: Discussionmentioning
confidence: 53%
“…Endometrial receptivity is essential for successful implantation and establishment of pregnancies in both natural and ART cycles [20]. There are still no accepted criteria for evaluating endometrial receptivity in IVF patients.…”
Section: Discussionmentioning
confidence: 99%
“…В ряде исследований [26,32] выявлена корреля-ция между недостаточной толщиной преовуляторно-го эндометрия (<8 мм) и нарушением его васкуляри-зации в виде высокорезистентного кровотока (воз-растание индексов RI и PI), снижения визуализации мелких артериальных сосудов (базальных и спираль-ных артерий) и уменьшения конечной диастоличе-ской скорости в маточных артериях. Однако другие исследователи [33,34] не смогли подтвердить зави-симость показателей кровотока от отставания роста эндометрия в пролиферативной фазе цикла.…”
Section: маточный кровоток и эндометриальная рецептивностьunclassified